Synthesis and Characterization of Methylammonium Lead Bromide Perovskite Based Photovoltaic Device - Shaily Choudhary; Shalini Tomar; Depak Kumar; Sudesh Kumar; Ajay Singh Verma (East European Journal of Physics, 2021)
Hybrid electronic devices give a reasonable path for feasible power sources and other further applications due to its easy arrangement, preparation, producing, ease of materials, and less environmental impact. In this paper, we have discussed electrical properties of hybrid bromide perovskite nanoparticles and current progressions in perovskite photovoltaic devices have also been discussed. In order to fabricate, low-temperature solution-processed devices using one-step spin coating methods play a key role in producing uniform thin films. The spin coating technique has been used for the deposition of the precursor solution including methylammonium bromide (MABr) and lead bromide (PbBr2) with molar ratio (3:1) to prepare the thin films onto FTO-substrate. One-step solution processes has been used for deposition of the CH3NH3PbBr3 absorber layers and have explained an overview of material composition, deposition technique and the architecture of the device, the selection of charge transport layer and electrode.